ADOLESCENTS' PERSONAL AUTONOMY AND INTENTIONS ON DENTAL AND ORAL HEALTH MAINTENANCE BEHAVIOR - Nita Sofia Rakhmawati; Irwan Budiono; Eunike Raffy Rustiana; Ani Subekti (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: Oral health problems are behavioral problems. One of the groups prone to dental and mouth problems is teenagers. The purpose of this study was to analyze the relationship between intention and personal autonomy with the behavior of maintaining oral health in adolescents.Method: This study was an analytic survey study with a cross sectional study approach. The subjects of this study were teenagers at Texmaco Semarang Vocational School, totaling 90 students with a total sampling technique. The research instrument used was a questionnaire. Data analysis was carried out by univariate analysis (frequency distribution) to explain the characteristics and results of each variable and bivariate analysis using the Spearman rank correlation test to see the relationship between the two variables.Result: The results of the study show female respondents have a higher intention/motivation in maintaining dental health compared to male respondents. Female respondents tend to prefer to decide for themselves in relation to dental health care compared to male respondents. Female respondents are better at maintaining dental health, compared to male respondents. Intention and personal autonomy are related to adolescent actions in maintaining dental and oral health with p-value 0.000 <0.05.Conclusion: Behavior has an important role in public health status. Intention as a major predictor of behavior. Personal autonomy contributes greatly to behavior change.